Influence of Complex Training Design on Acute Postactivation Performance Enhancement of Jump Squat and Ballistic Bench Throw Performance in Developing Team-Sport Athletes. Issue 5 (May 2023) - Poulos, Nick; Haff, G. Gregory; Nibali, Maria; Norris, Dean; Newton, Robert
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Poulos, N, Haff, GG, Nibali, M, Norris, D, and Newton, R. Influence of complex training design on acute postactivation performance enhancement of jump squat and ballistic bench throw performance in developing team-sport athletes. J Strength Cond Res 37(5): 969–979, 2023—The effect of complex training (CT) session design on acute postactivation performance enhancement (PAPE) of loaded jump squat(s) (JS) and ballistic bench throw(s) (BBT) was examined. This study further investigated whether relative strength is a moderating factor in PAPE in response to 3 distinct CT protocols. Fourteen Australian Football League (AFL) Academy athletes performed 3 different protocols comprising 85% 1 repetition maximum (1RM) back squats and bench press, and 30% 1RM loaded JS and BBT, differing in the sequencing of exercise order (i.e., complex pairs performed in isolation or with additional exercise interspersed within the intracomplex recovery period) and duration of the intracomplex recovery (2.5, 5, or 15 minutes). Differences in JS and BBT performance between CT protocols were trivial except for JS eccentric depth and eccentric impulse where small to moderate substantial differences were observed between protocols 2 and 3 in various sets; a small difference was observed between protocols 1 and 3 for eccentric depth. Small differences between protocols 1 and 2 were observed in set 1 in BBT peak velocity (ES = −0.26) and peak power (W·kg −1 ) (ES = −0.31). Small magnitudes of PAPE and decrements in performance were observed in some variables within protocols, yet effects across sets were inconsistent. Relative strength was negatively associated with JS performance (i.e., stronger athletes demonstrated a lower magnitude of PAPE) yet positively associated with PAPE of BBT peak force (N·kg −1 ) and peak power (W·kg −1 ). Alternating lower-body and upper-body complex sets and performance of ancillary exercise within the intracomplex recovery does not contribute to cumulative fatigue throughout the session and does not detrimentally affect subsequent JS and BBT performance. The manipulation of complex-set sequences offers practitioners a time-efficient means of providing both lower-body and upper-body heavy-resistance and ballistic training stimuli to achieve chronic training adaptations in maximal strength and power, with targeted improvements in specific kinetic and kinematic variables.